CONSUMER ETHNOCENTRISM AMONG YOUNG POLISH CONSUMERS - Tomasz Zalega (Acta Scientiarum Polonorum. Oeconomia, 2019)
This article is a research exercise examining consumer ethnocentrism among young Polish consumers. Its primary goal is to identify ethnocentric attitudes and behaviours of young people. The study consists of two parts: theoretical and empirical. The first one explains the concept and essence of ethnocentrism as a consumer trend, building upon a critical analysis of literature. The second, major part is empirical. The basis for conclusions is provided by the research material from a questionnaire-based survey that was conducted among young consumers. Undertaking such a research project is justified since ethnocentric tendencies have a direct impact on purchase decisions of consumers, including young people, while making it difficult for enterprises on the market to develop marketing strategies.